2020
DOI: 10.1126/science.aau6481
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell–derived hepcidin sequesters iron from the microbiota to promote mucosal healing

Abstract: Bleeding and altered iron distribution occur in multiple gastrointestinal diseases, but the importance and regulation of these changes remain unclear. We found that hepcidin, the master regulator of systemic iron homeostasis, is required for tissue repair in the mouse intestine after experimental damage. This effect was independent of hepatocyte-derived hepcidin or systemic iron levels. Rather, we identified conventional dendritic cells (cDCs) as a source of hepcidin that is induced by microbial stimulation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 30 publications
2
68
0
1
Order By: Relevance
“…Several lines of evidence have established a link between inflammation and oxidative stress ( Khomich et al, 2018 , van den Brand et al, 2014 ) . In this context, we have shown that hepcidin, the key iron regulatory molecule, plays a major role during inflammatory processes ( Bessman et al, 2020 ). We also addressed the role and management of a dysregulated iron state in COVID-19 pathogenesis ( Edeas et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence have established a link between inflammation and oxidative stress ( Khomich et al, 2018 , van den Brand et al, 2014 ) . In this context, we have shown that hepcidin, the key iron regulatory molecule, plays a major role during inflammatory processes ( Bessman et al, 2020 ). We also addressed the role and management of a dysregulated iron state in COVID-19 pathogenesis ( Edeas et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Iron efflux from cells is critical for body iron homeostasis and is negatively controlled by hepcidin, a peptide hormone that inactivates ferroportin in macrophages, enterocytes and other target cells [ 8 ] ( Figure 1 ). Circulating hepcidin is synthesized by hepatocytes in the liver; however, hepcidin is also locally produced in other tissues and appears to have critical cell-autonomous functions [ 9 , 10 , 11 ]. The hepcidin-encoding HAMP gene is primarily induced in response to iron or inflammatory signals [ 8 ].…”
Section: Systemic Iron Metabolismmentioning
confidence: 99%
“…188,189 Conversely, iron-deficient diets in experimental systems seem to favour the growth of protective microorganisms. 107,166…”
Section: Targeting the Pathogenmentioning
confidence: 99%